2019
DOI: 10.1016/j.whi.2019.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Job Holding and Mental Health among Low-Income Mothers

Abstract: a b s t r a c tPurpose: Studies have found considerable heterogeneity in the links between employment and mental health, finding that certain work conditions, such as nonstandard schedules and low job quality, are linked with poorer mental health. One largely overlooked facet of work is multiple job holding. In this article, we examine the link between multiple job holding and mental health among low-income mothers. Methods: We used data from the Fragile Families and Child Wellbeing Study (n ¼ 7,844 person-wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 27 publications
0
15
1
Order By: Relevance
“…Further, while gender is likely an important moderator, it has not received significant attention. The few scholars who have considered gender either found no differences in MJH experiences (Jamal et al, 1998) or found the experience to be worse for women such that male teachers earned more “outside employment pay” than female teachers (Betts, 2004), and MJH mothers were more likely to experience depression and less life satisfaction than SJH mothers (Bruns & Pilkauskas, 2019). Looking across studies, it appears that MJHers with higher social-status indicators (e.g., more experience, male; Chattopadhyay, Tluchowska, & George, 2004) have more enriching outcomes.…”
Section: A Systematic Review Of the Mjh Literaturementioning
confidence: 99%
“…Further, while gender is likely an important moderator, it has not received significant attention. The few scholars who have considered gender either found no differences in MJH experiences (Jamal et al, 1998) or found the experience to be worse for women such that male teachers earned more “outside employment pay” than female teachers (Betts, 2004), and MJH mothers were more likely to experience depression and less life satisfaction than SJH mothers (Bruns & Pilkauskas, 2019). Looking across studies, it appears that MJHers with higher social-status indicators (e.g., more experience, male; Chattopadhyay, Tluchowska, & George, 2004) have more enriching outcomes.…”
Section: A Systematic Review Of the Mjh Literaturementioning
confidence: 99%
“…It is unlikely that a mother working regular 8-hour workdays would be able to see her infant at these regular intervals for feeds. As well, approximately 16% of mothers with young children hold multiple jobs, which can further reduce the time that these mothers are able to spend with their children (9). In any circumstance, whether a child is 1 month old or 10 years old, spending less time together as a family unit can act as a hinderance to bonding.…”
Section: The Social Determinants Of Health and Rsvmentioning
confidence: 99%
“…Numerous studies, both within and outside the family stress model framework, have linked economic hardship, material hardship, or financial strain to caregivers’ mental health, psychological well-being, or emotional distress (Masarik & Conger, 2017; Perzow et al, 2018). Psychological or affective responses including depressive mood (Rigotti et al, 2014), life satisfaction (Bruns & Pilkauskas, 2019), and more general psychological distress including generalized anxiety disorder (Benach et al, 2014) have been linked to conditions of employment such as job insecurity, involuntary job loss, multiple job holding, and temporary or otherwise contingent employment. In an urban sample of low-income mothers of young children, Coley and Lombardi (2014) found that mothers’ wages, and not their health insurance access or employment stability, had direct effects on their physical and mental health.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When the income earned by individual caregivers appears in parenting stress models, it is typically modeled as a predictor of economic hardship or financial strain (Jackson et al, 2000; Mistry et al, 2008), rather than as a direct source of emotional and/or parenting distress. However, some researchers have identified direct relationships between specific aspects of caregivers’ work, such as wages, nonstandard work hours, and working multiple jobs, and caregivers’ emotional or physical states (Bruns & Pilkauskas, 2019; Coley & Lombardi, 2014). Building on the premise of a direct connection between wages and the well-being of caregivers (Bruns & Pilkauskas, 2019; Coley & Lombardi, 2014), we explored whether the role of earned wages in the lives of families in low-income households might extend beyond caregivers’ emotional states to parenting practices and, thereby, to the behaviors of the children in their care.…”
Section: Introductionmentioning
confidence: 99%